ETIKA MENDIDIK ANAK DALAM PANDANGAN AGAMA KRISTEN BERDASARKAN AMSAL 19:18 - Neti Pera Br. Berutu; Bobby Lumbantobing (CV. Denasya Smart Publisher, 2024)
The character of a child is of utmost importance in social life because it manifests in every behavior in daily life. This research aims to understand the ethics of child education from a Christian perspective, specifically related to Proverbs 19:18. Education is a fundamental foundation for all humans, one aspect of which is